126k views
5 votes
What is the Solution?

What is the Solution?-example-1
User Bigpotato
by
5.8k points

2 Answers

6 votes

Answer:

w = 2 and w = 6

Explanation:

Given


(w)/(2w-3) =
(4)/(w) ( cross- multiply )

w² = 4(2w - 3) ← distribute

w² = 8w - 12 ( subtract 8w - 12 from both sides )

w² - 8w + 12 = 0 ← in standard form

(w - 2)(w - 6) = 0 ← in factored form

Equate each factor to zero and solve for w

w - 2 = 0 ⇒ w = 2

w - 6 = 0 ⇒ w = 6

User Daniel Moses
by
5.0k points
3 votes

Answer: w=2 and 2=6

Explanation:

If you substitute 6 and 2 in for w they both work, making c the correct answer

User Suman Bogati
by
5.0k points